Contracting Marriage by Proxy in the Roman Catholic Church by a Polish Citizen outside the Territory of the Republic of Poland - Świto, Lucjan; Tomkiewicz, Małgorzata (Studia Warmińskie, 2020)
This paper describes issues related to contracting marriage by proxy outside the territory of the Republic of Poland by Catholics who are Polish citizens. It attempts to answer the question of whether the faithful of the Roman Catholic Church who are citizens of Poland can contract marriage outside the territory of Poland and whether such marriage can have legal status according to Polish law. To this end, an analysis of the canon law and Polish regulations was performed, taking into consideration the private international law. According to the analysis findings, the faithful of the Catholic Church who are Polish citizens can contract marriage by proxy in the Latin Church outside the territory of Poland. However, whether such marriage will have legal effect in Poland will depend on whether contracting marriage by proxy is llowable in a given country and whether the formal obligations required by the law for matrimonium per procura have been fulfilled.